Characterization of a High Hierarchical Regulator, PtrGATA12, Functioning in Differentially Regulating Secondary Wall Component Biosynthesis in Populus trichocarpa - Ren, Mengxuan; Zhang, Yang; Liu, Cong; Liu, Yingying; Tian, Shuanghui; Cheng, He; Zhang, Huaxin; Wei, Hairong; Wei, Zhigang (Frontiers in Plant Science, 2021)
In plants, GATA transcription factors (TFs) have been reported to play vital roles in to a wide range of biological processes. To date, there is still no report about the involvement and functions of woody plant GATA TFs in wood formation. In this study, we described the functional characterization of a Populus trichocarpa GATA transcription factor (TF), PtrGATA12, which encodes a nuclear-localized transcriptional activator predominantly expressing in developing xylem tissues. Overexpression of PtrGATA12 not only inhibited growths of most phenotypic traits and biomass accumulation, but also altered the expressions of some master TFs and pathway genes involved in secondary cell wall (SCW) and programmed cell death, leading to alternated SCW components and breaking forces of stems of transgenic lines. The significant changes occurred in the contents of hemicellulose and lignin and SCW thicknesses of fiber and vessel that increased by 13.5% and 10.8%, and 20.83% and 11.83%, respectively. Furthermore, PtrGATA12 bound directly to the promoters of a battery of TFs and pathway genes and activated them; the binding sites include two cis-acting elements that were specifically enriched in their promoter regions. Taken together, our results suggest PtrGATA12, as a higher hierarchical TF on the top of PtrWND6A, PtrWND6B, PtrMYB152 and PtrMYB21, exert a coordinated regulation of SCW components biosynthesis pathways through directly and indirectly controlling master TFs, middle-level TFs and further downstream pathway genes of the currently known hierarchical transcription network that governs SCW formation.